The S RNA segment of lymphocytic choriomeningitis virus codes for the nucleoprotein and glycoproteins 1 and 2. - Riviere, Y (1985)
The lymphocytic choriomeningitis virus (LCMV) genome consists of a large RNA segment and a small RNA segment. The three major structural proteins of this virus are an internal nucleoprotein and two surface glycoproteins. Intertypic reassortants between the Armstrong and WE strains of LCMV were made to map proteins encoded by the LCMV genome segments. Using monoclonal antibodies specific for the nucleoprotein and the glycoproteins of WE and Armstrong, we showed that the small RNA segment of LCMV codes for the three major structural polypeptides.